Método peculiar de governança corporativa por controlador Fuzzy Matriz Slack - Umeda, Wilson Leiki (2011)
From the logic of inductive reasoning were tested in this work, the development strategies of the company ALFA by a Peculiar Method of Corporate Governance called Fuzzy Controller Matrix Slack (FCMS). The applicability of this process was focused on the development of globalization processes that are present within the company as a whole, causing the development of analysis tools focused on managing people and between people. Thus, we sought to develop a systematic review panel called Panel Interactive Heuristic that based on the Matrix Slack and a Panel of Aggregation of the results. The problem that presents itself is centered on the question: When performing the conversion of deterministic and fragmented knowledge to a model based on self-organization of knowledge inherent to human interaction is an opportunity to review the development strategies of a company? The outcome in the Beta systematization of the company for use in Governance FCMS was generated multiplier "1 ", while systems of rational use of deterministic knowledge of computational logic pointed Beta "0.685". In self-organization by FCMS of inductive reasoning, the dissent led to a consensus strategic competitive identified as "appropriate" in the projections for the strategic development of the company called alpha.